A Critical Review of the Science and Practice of Competency Modeling. (March 2013) - Stevens, Gregory W.
As an alternative to traditional job analysis, the practice of competency modeling may be appealing to scholars and practitioners of human resource development (HRD) to serve as the foundation for many HRD activities. Among some of its advantages are a more explicit focus on performance and development that is aligned with organizational strategy, fuller integration with human resource systems, and a focus on broad work roles and functions instead of discrete jobs. Unfortunately, the use of competency models is often hindered as a result of conceptual ambiguity, a lack of methodological rigor in the development of such systems, and psychometric issues. The current integrative literature review seeks to clarify the practice of competency modeling within the context of HRD through a critical analysis of its foundations, conceptual and definitional issues, and potential barriers to use while providing the current state of the science and best practices.